2018
DOI: 10.1002/bsd2.36
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability value creation in frugal contexts to foster Sustainable Development Goals

Abstract: The 17 Sustainable Development Goals (SDGs) stress unsolved global topics such as mitigating poverty and exclusion. Inclusive approaches often highlight frugal innovations for the Base of the Pyramid and low income markets, mainly offered by private sector. In the contexts of sustainability, the private sector is both, a major driver of exclusionary processes as well as for enforcing new inclusive solutions enhancing quality of life, participation, and incomes. So it is of interest if and how the business sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 47 publications
0
43
0
5
Order By: Relevance
“…Similarly, Redman () shows possible strategies for firms to make progress in the concept of CSR by introducing the UN_SDGs. Arnold () identified that 50 frugal innovations have been made by firms, which have implemented UN_SDGs. They have supported that the social engagement might create appropriate conditions for innovations to small‐ and medium‐sized enterprises, whereas multinational enterprises (MNEs) are driven more by institutional incentives to make innovations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Similarly, Redman () shows possible strategies for firms to make progress in the concept of CSR by introducing the UN_SDGs. Arnold () identified that 50 frugal innovations have been made by firms, which have implemented UN_SDGs. They have supported that the social engagement might create appropriate conditions for innovations to small‐ and medium‐sized enterprises, whereas multinational enterprises (MNEs) are driven more by institutional incentives to make innovations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hence, access to internet is very limited for those that form part of the category of socially excluded individuals.The lack of developed or developing infrastructure in rural areas also impact on the level of access to internet, as most people have to rely on public libraries and paid internet cafes to access the internet and are limited in amount of time that they actually have access to this. However, countries, regions or cultures having or using higher levels of technology, education, basic services, food, expectation of life and so on are very different from countries, regions or cultures developed otherwise; mostly indicated by higher levels of poverty, less education, limited basic services and expectation in life or specific diseases (Arnold, 2018). Thus, it can be said that the major challenge that South Africa faces with regard to social exclusion and online platforms can be addressed by wider access to internet.…”
Section: Internet Access In South Africamentioning
confidence: 99%
“…Social, economic, political and cultural contexts are interwoven and determining one another. Thus, social exclusion often relates to both a lack of material resources and/or capabilities, such as insufficient social participation or integration as well as access to services (health and education) and necessary goods, and the consequent lack of power (Arnold, 2018).…”
Section: The Impact Of Sharing Economies On Social Exclusion and Economic Marginalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution “Sustainability value creation in frugal contexts to foster Sustainable Development Goals” by Marlen Gabriele Arnold (—this issue) adopts a value creation perspective regarding the realization and enforcement of sustainable development and the SDGs. In so doing, the study highlights the role of mitigating social exclusion and fostering inclusion approaches as well as the relevance of frugal contexts.…”
Section: Papers In This Special Issuementioning
confidence: 99%